Chronic hypopituitarism is uncommon in survivors of aneurysmal subarachnoid haemorrhage. (18th July 2014) - Hannon, M. J.; Behan, L. A.; O'Brien, M. M.; Tormey, W.; Javadpour, M.; Sherlock, M.; Thompson, C. J.
Summary Objective The incidence of hypopituitarism after aneurysmal subarachnoid haemorrhage (SAH) is unclear from the conflicting reports in the literature. As routine neuroendocrine screening for hypopituitarism for all patients would be costly and logistically difficult, there is a need for precise data on the frequency of hypopituitarism and on factors which might predict the later development of pituitary dysfunction. We aimed to: (i) Establish the incidence of long‐term hypopituitarism in patients with aneurysmal SAH. (ii) Determine whether data from patients' acute admission with SAH could predict the occurrence of long‐term hypopituitarism. Design One hundred patients were studied prospectively from the time of presentation with acute SAH. Plasma cortisol, plasma sodium and a variety of clinical and haemodynamic parameters were sequentially measured for the first 12 days of their acute admission. Forty‐one patients then underwent dynamic pituitary testing at median 15 months following SAH (range 7–30 months), with insulin tolerance test (ITT) or, if contraindicated, a glucagon stimulation test (GST) plus short synacthen test (SST). If symptoms of cranial diabetes insipidus (CDI) were present, a water deprivation test was also performed. Results Forty‐one patients attended for follow‐up dynamic pituitary testing. Although 14 of 100 had acute glucocorticoid deficiency immediately following SAH, only two of 41 had long‐term adrenocorticotrophic hormone (ACTH) deficiency and four of 41 had growth hormone (GH) deficiency. None were hypothyroid or gonadotrophin deficient. None had chronic CDI or hyponatraemia. There was no association between acute glucocorticoid deficiency, acute CDI or acute hyponatraemia and long‐term pituitary dysfunction. Conclusion Both anterior and posterior hypopituitarism are very uncommon following SAH and are not predicted by acute clinical, haemodynamic or endocrinological parameters. Routine neuroendocrine screening is not justified in SAH patients.